Association between SLC11A1 (NRAMP1) polymorphisms and susceptibility to tuberculosis in Chinese Holstein cattle. (March 2017) - Liu, Kaihua; Zhang, Bin; Teng, Zhaochun; Wang, Youtao; Dong, Guodong; Xu, Cong; Qin, Bo; Song, Chunlian; Chai, Jun; Li, Yang; Shi, Xianwei; Shu, Xianghua; et al.
Abstract: We investigated the associations between SLC11A1 polymorphisms and susceptibility to tuberculosis (TB) in Chinese Holstein cattle, using a case-control study of 136 animals that had positive reactions to TB tests and showed symptoms and 96 animals that had negative reactions to tests and showed no symptoms. Polymerase chain reaction (PCR) sequencing and the restriction fragment length polymorphism (RFLP) technique were used to detect and determine SLC11A1 polymorphisms. Association analysis identified significant correlations between SLC11A1 polymorphisms and susceptibility/resistance to TB, and two genetic markers for SLC11A1 were established using PCR-RFLP. Sequence alignment of SLC11A1 revealed seven single-nucleotide polymorphisms (SNPs). This is the first report of Mae II PCR-RFLP markers for the SLC11A1 -SNP3 site and Pst I PCR-RFLP markers for the SLC11A1 -SNP5 and SLC11A1 -SNP6 sites in Chinese Holstein cattle. Logistic regression analysis indicated that SLC11A1 -SNP1, SLC11A1 -SNP3, and SLC11A1 -SNP5 were significantly associated with susceptibility/resistance to TB. Two genotypes of SLC11A1 -SNP3 were susceptible to TB, whereas one genotype of SLC11A1 -SNP1 and two genotypes of SLC11A1 -SNP5 were resistant. Haplotype analysis showed that nine haplotypes were potentially resistant to TB. After Bonferroni correction, three of the haplotypes remained significantly associated with TB resistance. SLC11A1 is a useful candidate gene related to TB in Chinese Holstein cattle.